Fruit commodity development in Goma District through farmer-based improved fruit seedling supply system: Experiences from IPMS - Baredo, Y.; Berhe, Kahsay; Hoekstra, Dirk (International Livestock Research Institute, 2010)
In Goma, fruits considerably contribute in improving the nutritional status and income of the community. However, its production and productivity has been very low. The objective of this case study is to share best practices and lessons learned from farmer-based improved fruit seedlings supply system that could contribute to enhance fruit production in Goma Pilot Learning Woreda (PLW). The assessment result highlights that fruits production in Goma is a recent phenomenon and all fruit farmers got their first planting material from unknown sources and hence agronomic and cultural practices required for each fruit type is less known. Consequently, constraints such as extended periods to fruiting, failure to set fruits, unmanageable fruit tree height, diseases and pests, low yield, etc. are very common. Above all, introduction of various fruits to Goma Woreda was made much earlier than the institutional, skill and knowledge of the OoARD (the Office of Agriculture and Rural development) staff handling them. In addition, key technical limitation to fruits development identified through participatory commodity development approach includes scarcity of improved planting materials, large canopies, poor quality fruits, long time to maturity, among others. IPMS and OoARD initiated farmers-based improved fruits planting materials multiplication and distribution system in trying to solve the problem. Six model farmers (3 female, 3 male) were trained and engaged in grafting avocado and produced 2,052 grafted avocado seedlings from internationally known varieties such as Hass, Ettinger, and Fuerte which were sold to 163 households in 28 Peasant Associations (Pas) at Birr 25 per seedling. The farmers earned Birr 42,000 among them in total. Also mother trees of Hass, Ettinger and Fuerte were established in each model farmer’s plot for sustainable scion supply. Taking the advantage of this successful demonstration, OoARD started a scaling out program by including 3 additional model farmers. The 9 model farmers have now raised 17,000 avocado and mango root stock seedling at their own cost amounting to Birr 85,000 which will be ready for grafting starting from January 2010. In addition 3 copy farmers in Kilole PA are also engaged in improved fruits seedlings production. The effort demonstrated that farmers could be good sources for technology multiplication and distribution, which has been a key challenge in technology uptake not only for fruits but for many other commodities in Ethiopia.